The effect of bright light therapy on glycemic control and cortisol rhythmicity in depression: a randomized controlled trial - Fang, Jie; Li, Xinyu; Zhu, Shukun; Hu, Qinghong; Wang, Ting; Yu, Jiakuai; Qin, Ximing; Zhu, Daomin (Frontiers in Psychiatry, 2026)
BackgroundDepressed patients with comorbid metabolic disorders have poorer quality of life and prognosis. Pharmacological interventions carries risks of liver and kidney toxicity, which highlights the need for safer non-pharmacological alternatives. Experimental data suggest that light exposure modulates cortisol secretion, thereby influencing metabolic outcomes in depression. We hypothesized that bright light therapy may ameliorate metabolic disturbances by modulating cortisol secretion.MethodsIn this randomized controlled trial, hospitalized patients with depression were assigned to receive either bright light therapy (BLT) or dim-light control condition. The pre−specified primary endpoint was the change in fasting blood glucose (FBG) and cortisol rhythm indices from baseline to post−treatment. Secondary endpoints included changes in other glycolipid parameters, and scores on the Hamilton Depression (HAMD) and Anxiety (HAMA) scales. Treatment effects were evaluated using linear mixed−effects models with baseline adjustment.ResultsAfter the 2−week intervention, the BLT group showed a significant reduction in fasting blood glucose (95% CI: 0.280 to 0.600; p < 0.001) and cortisol mesor (95% CI: −2.677 to −0.064; p = 0.040) compared to the control group. Within the BLT group, the change in FBG was positively associated with the change in cortisol mesor after adjusting for covariates (β = 0.053, 95% CI: 0.016 to 0.122, p = 0.036).ConclusionsThe findings of this study support a potential mechanism whereby BLT modulates cortisol rhythmicity, which in turn may contribute to improved glycemic control, pointing to its potential therapeutic benefit for addressing metabolic disturbances in depression.Clinical Trial Registrationhttps://www.chictr.org.cn/bin/project/edit?pid=260569, identifier ChiCTR2500097364.